2011
DOI: 10.4028/www.scientific.net/amm.117-119.1496
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Automotive Interior Trim Materials Based on Moldflow

Abstract: The influence of different materials on the formability of plastic injection molding has been studied in current work. The automotive glove box trim cover was chosen as analytical model. This study has been focused on the influence on fill time, warpage, sink mark depth and clamp force of different materials. PP+T15, PP+T20, PP+T25, PP+T30, PP+T35, PP+T40 and ABS+PC were used for analysis in this study. The injection molding processes of automotive interior trim of different materials were analyzed by using Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Recognizing this critical gap, the present study is poised to embark on an investigation aimed at characterizing the size effect exhibited by four polymers: polycarbonate acrylonitrile butadiene styrene (PC/ABS), ASA, PLA, and nylon. Each of these polymers holds distinctive applications in a diverse array of industries; for instance, PC/ABS finds prominent utility in blow-molded seatbacks [36] and automotive exterior components [37], while ASA is widely employed in the automotive industry for its excellent performance in exterior applications [38], as well as in the construction sector [39]. Based on initial findings, it has been suggested that recycling PLA has an environmental impact that is 50 times more favorable than composting and 16 times more favorable than combustion, which is considered quite sustainable [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing this critical gap, the present study is poised to embark on an investigation aimed at characterizing the size effect exhibited by four polymers: polycarbonate acrylonitrile butadiene styrene (PC/ABS), ASA, PLA, and nylon. Each of these polymers holds distinctive applications in a diverse array of industries; for instance, PC/ABS finds prominent utility in blow-molded seatbacks [36] and automotive exterior components [37], while ASA is widely employed in the automotive industry for its excellent performance in exterior applications [38], as well as in the construction sector [39]. Based on initial findings, it has been suggested that recycling PLA has an environmental impact that is 50 times more favorable than composting and 16 times more favorable than combustion, which is considered quite sustainable [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…rozstawu otworów montażowych) [4][5][6]. Wynika to z tego, że tworzywa sztuczne mają niższą sztywność, a konstruktorzy oczekują od elementów produkowanych metodą wtryskiwania dokładności niewiele gorszej niż w przypadku wyrobów metalowych [7].…”
unclassified